Pengaruh Iklim Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. Astra Motor Internasional - Rhoni Ilham Tampubolon (Economics, Business and Management Science Journal, 2022)
The research objective to be achieved by the authors of this study is to determine whether organizational climate has a positive and significant effect on employee performance at PT. Astra Motor Internasional, does Job Satisfaction have a positive effect on employee performance at PT. Astra Motor Internasional, and whether the Organizational Climate and Job Satisfaction have a positive and significant effect on the performance of employees at PT. Astra Motor International. The population and sample in this study were employees of PT. Astra Motor International, amounting to 104 employees. The data analysis techniques used were Technical Data Analysis, Data Analysis Test, Multiple Linear Regression Analysis Test, Classical Assumption Test and Hypothesis Test, namely t test (partial), f test (simultaneous) and the coefficient of determination. Based on the results of the partial test (t test), it can be concluded that Organizational Climate has a significant effect on employee performance. Job Satisfaction has a significant influence on employee performance. Based on the results of the F test, it can be concluded that the variables of Organizational Climate and Job Satisfaction simultaneously have a significant effect on employee performance. The R-Square value obtained is 0.424, indicating that about 42.4% of the Y variable (Employee Performance) can be explained by the Organizational Climate variable (X1) and Job Satisfaction (X2).